Calculation-experimental method of determination of tribocontact parameters - Писаренко, В.Г.; Диха, К.О.; Скрипник, Т.К. (Problems of Tribology, 2016)
Presented results calculation-experimental methods of determination of tribocontact parameters at the dynamic contact of sphere and plane. In paper used method of imprints is for finding of the module of resiliency of rubber by a spherical standard and special loading device. In future this method is used for the receipt of dependences for determination of force of blow of sphere and plane, middle and maximal pressure. Resulted example of realization of the offered method.